Pengaruh Islamic Religiosity dan Halal Knowledge terhadap Purchase Intention Kosmetik Halal Dimediasi oleh Attitude terhadap Produk Halal di Indonesia - Lisa Adriani; Ma'ruf (AL-MUZARA'AH, 2020)
Indonesia is the largest Muslim country in the world. Every Muslim must consume halal products. The trend in Indonesian society that is developing now is the hijrah trend. People change lifestyles to become more aware and concerned with the halal of a product. The hijrah trend makes halal standardization develop on food and beverages, services and lifestyle (halal cosmetics). One of the halal cosmetics sold in Indonesia is Make Over Brand Cosmetics. Make Over has been registered in the Indonesian Ulema Council as halal cosmetics that can provide security for Muslim. The purpose of this study is to analyze the direct relationship between Islamic religiosity and halal knowledge variables on the attitude and purchase intention variables. Then analyze the indirect relationship between Islamic religiosity and halal knowledge variables on the purchase intention variable that is mediated by the attitude variable. The sampling technique is purposive sampling with 185 respondents. Data analysis techniques using quantitative analysis with analysis tools SmartPLS 3.0. The results of the analysis showed a significant positive direct relationship between Islamic religiosity variables and halal knowledge on the purchase intention and attitude variables. Then there is also an indirect relationship with partial mediation by the attitude variable.